2010
DOI: 10.1097/scs.0b013e3181e20860
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Tube Fixation Methods for Optimal Stability

Abstract: Accidental extubation of an intubated patient is a serious consideration in the surgical patient. Adequate fixation in the intubated patient is essential to prevent potentially life-threatening complications. Several methods of endotracheal tube fixation have been described in the literature. In this study, we examine 3 common methods of fixation: adhesive tape alone, suture, and tape-suture. Testing occurred in a laboratory setting with 2 fresh cadavers. Endotracheal tubes were inserted, using the methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In combat casualties, this is a common cause of preventable death on the battlefield 9. Movement of the ETT after successful intubation leading to accidental extubation or tube displacement are serious complications associated with high morbidity 2. Therefore, ETT should be quickly and effectively secured before any movement of the patient, especially in prehospital or combat settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combat casualties, this is a common cause of preventable death on the battlefield 9. Movement of the ETT after successful intubation leading to accidental extubation or tube displacement are serious complications associated with high morbidity 2. Therefore, ETT should be quickly and effectively secured before any movement of the patient, especially in prehospital or combat settings.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used methods include adhesive tapes, non-adhesive tapes (twills), gauze bandage rolls and various commercially designed devices. Previous studies found that all these common techniques are acceptably stable 2–6. Although adhesive tapes have been shown to provide sufficient resistance to extubation, they are time consuming to apply, require significant preparation time and may be difficult to use in the prehospital, trauma and combat settings due to sweat, blood and dirt preventing appropriate adhesion 6.…”
Section: Introductionmentioning
confidence: 99%
“…58 Overall, the data suggest that it is less expensive, more convenient, and just as effective to use standard white surgical tape to secure the ETT as any other alternative method. 54, 56 Unfortunately, none of these studies has examined the amount or effect of lateral and longitudinal movement of the ETT based on securement method.…”
Section: Methodsmentioning
confidence: 99%
“…Accidental extubation can lead to catastrophic events, especially in head and neck surgeries, when airway access is difficult intraoperatively. 1 Providing anesthesia to the patients with facial hair or beard is always a challenge because, in addition to difficult mask ventilation, tube fixation is also tricky. Some people keep a beard because of religious beliefs, while others keep it as a symbol of fashion or respect, so they do not consent to shave.…”
mentioning
confidence: 99%